2017
DOI: 10.3390/molecules22122137
|View full text |Cite
|
Sign up to set email alerts
|

Using the SPE and Micro-HPLC-MS/MS Method for the Analysis of Betalains in Rat Plasma after Red Beet Administration

Abstract: The objective of this study was to develop a simple and reproducible method for the qualitative and quantitative analysis of betalains in plasma samples, based on Solid Phase Extraction (SPE) and micro-high performance liquid chromatography coupled with mass spectrometry (micro-HPLC-MS/MS). The eight betalain compounds detected and quantified were characterized in the fortified rat blood plasma samples. The developed method showed a good coefficient of determination (R2 = 0.999), good recovery, precision, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…However, beetroots are the main source of betanin, and this major red-violet beetroot pigment emerged as a powerful antioxidant phytochemical [28]. Studies in animal modelswere more conclusive about the plasma bioavailability and biological effect of purified betanin intake [35,51]. Betanin and betalain bioavailability in humans is considered low; however, the betanin mechanism regarding absorption, metabolism, and excretion routes, still requires elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…However, beetroots are the main source of betanin, and this major red-violet beetroot pigment emerged as a powerful antioxidant phytochemical [28]. Studies in animal modelswere more conclusive about the plasma bioavailability and biological effect of purified betanin intake [35,51]. Betanin and betalain bioavailability in humans is considered low; however, the betanin mechanism regarding absorption, metabolism, and excretion routes, still requires elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, after lactic acid fermentation by Lactobacillus sp., six betalains were detected in the obtained juices (Czyżowska at al., 2006). Furthermore, in another study, eight betalain compounds were found in the obtained juice during spontaneous fermentation (Sawicki et al, 2017). In the same study, five betalains were detected in fresh juice; of these, four compounds belong to the betacyanins group, and one compound belongs to the betaxanthins group (Sawicki et al, 2017).…”
Section: The Profile and Content Of Betalains In Red Beet Productsmentioning
confidence: 93%
“…Furthermore, in another study, eight betalain compounds were found in the obtained juice during spontaneous fermentation (Sawicki et al, 2017). In the same study, five betalains were detected in fresh juice; of these, four compounds belong to the betacyanins group, and one compound belongs to the betaxanthins group (Sawicki et al, 2017). The different numbers of identified betalains may be due to the use of different varieties of red beet.…”
Section: The Profile and Content Of Betalains In Red Beet Productsmentioning
confidence: 93%
“…In recent years, the root of the Beta vulgaris L. plant has attracted considerable attention as a functional health promoting food [Chhikara et al, 2019]. It is rich in valuable active compounds such as: betalains [Genga tharan et al, 2015;Khan & Giridhar 2015;Sawicki et al, 2016Sawicki et al, , 2017, phenolics [Kujala et al, 2002;Ninfali et al, 2017;Preczenhak et al, 2019;Ravichandran et al, 2012], saponins [Mikołajczyk--Bator et al, 2016], and fi ber [Lundberg et al, 2008]. Beet juice contains a high level of biologically available antioxidants and many trace elements such as potassium, magnesium, zinc, iron, calcium, phosphorus, sodium, as well as vitamins: niacin and biotin [Wootton-Beard & Ryan, 2011].…”
Section: Introductionmentioning
confidence: 99%